Modelling of JET DT experiments in ILW configurations. Issue 6 (14th February 2018) - Zagórski, R.; Czarnecka, A.; Ivanova‐Stanik, I.; Challis, C.; ,
Abstract : Numerical scan at constant β shows that core and scrape‐off layer (SOL) radiations do not depend on the plasma current ( I p ). Whereas the SOL radiation increases with seeding, the core radiation, however, does not continue to increase with seeding but rolls over at higher seeding rates in the simulations. The core plasma contamination by W ions is low, c W ≪ 10 −4 . When the seeding starts, an increase in radiation power leading to a reduction in P loss = ( P aux − P rad ) is observed, influencing the plasma confinement. The power scan at constant I p indicates that the core radiation, P plate, P SOL (and even SOL radiation), saturates with seeding. In addition, strong dilution with increasing seeding ( Z eff ≫ 3) and large W concentrations with increasing power are found. Comparing neon with nitrogen seeding, it is seen that neon leads to slightly larger total radiation than nitrogen. However, that is achieved with much higher plasma contamination ( Z eff ∼ 4–5) and dilution in the case of Ne, and simultaneously the power crossing the separatrix is lower for Ne than for N, indicating better H‐mode performance in N2 ‐seeded discharges.